2011
DOI: 10.1111/j.1755-0998.2011.03020.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid species identification of pygmy rabbits (Brachylagus idahoensis) from faecal pellet DNA

Abstract: The pygmy rabbit (Brachylagus idahoensis) is a small lagomorph of the western United States that specializes in sagebrush (Artemisia spp.) habitat. Intensive habitat loss and modification have increased the vulnerability of pygmy rabbit populations, but the current geographic distribution and population status remain unclear. To aid in detection and population monitoring, we developed a species identification test that uses mitochondrial DNA species-specific primers to distinguish among six sympatric lagomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…However, very few (if any) of these scats are likely to have produced a successful individual identification since all samples that amplified at less than 50% of the loci were removed from analyses, and PCR amplification success rates for carnivore samples older than 2 months were 0–39% (truex¯ = 19%; Piggott , Murphy et al ). Furthermore, DNA degradation rates are greater in wet (Piggott , Murphy et al , Brinkman et al ) and hot environments (Nsubuga et al , DeMay et al ) and less in dry and cold environments (Lucchini et al , Adams et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, very few (if any) of these scats are likely to have produced a successful individual identification since all samples that amplified at less than 50% of the loci were removed from analyses, and PCR amplification success rates for carnivore samples older than 2 months were 0–39% (truex¯ = 19%; Piggott , Murphy et al ). Furthermore, DNA degradation rates are greater in wet (Piggott , Murphy et al , Brinkman et al ) and hot environments (Nsubuga et al , DeMay et al ) and less in dry and cold environments (Lucchini et al , Adams et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al . () developed the mtDNA species ID test used in this study and found 72% PCR success for nonwinter pygmy rabbit pellet samples of unknown age (Adams et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…() developed the mtDNA species ID test used in this study and found 72% PCR success for nonwinter pygmy rabbit pellet samples of unknown age (Adams et al . ). Noninvasive genetic sampling and mtDNA species identification is also an important tool for monitoring the distribution of threatened New England cottontails (Kovach et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations